Colonizing the realm of words : the transformation of Tamil literature in nineteenth-century South India - Ebeling, Sascha (SUNY series in Hindu studies., 2010)
A true tour de force, this book documents the transformation of one Indian literature, Tamil, under the impact of colonialism and Western modernity. While Tamil is a living language, it is also India's second oldest classical language next to Sanskrit, and has a literary history that goes back over two thousand years. On the basis of extensive archival research, Sascha Ebeling tackles a host of issues pertinent to Tamil elite literary production and consumption during the nineteenth century. These include the functioning and decline of traditional systems in which poet-scholars were patronized by religious institutions, landowners, and local kings; the anatomy of changes in textual practices, genres, styles, poetics, themes, tastes, and audiences; and the role of literature in the politics of social reform, gender, and incipient nationalism. The work concludes with a discussion of the most striking literary development of the timeùthe emergence of the Tamil novel. --Book Jacket.